Rebellion and Representation: The Making of the Merthyr Tydfil Constituency, 1831–2. (14th July 2013) - Rowlands, Ted
The enfranchisement of Merthyr Tydfil as a single-borough constituency was made by the very last amendment to the third reform bill in the House of Commons in March 1832. The received view is that this was because the riotous and radical politics of the town compelled Whig ministers to recognize Merthyr's case. This article questions that view by examining how Whig ministers sought to maintain the difficult balance between carrying traditional county and rural interests and seeking to recognize the justifiable interests and demands of the fast growing industrial communities, of which Merthyr Tydfil was one. Whig ministers conceded individual cases in order to sustain support for the bill as a whole, and the final concession on Merthyr can be seen as a part of a process of negotiation. A town with a renowned history of radicalism owed its first civic achievement – parliamentary representation – rather less to its radicals and rather more to its counter-revolutionaries.